Analisis Yuridis Terhadap Akta Jual Beli yang Tidak Dibacakan Pejabat Pembuat Akta Tanah - Fitria, Rifka; Ardiyansyah, Amzar (Locus Journal of Academic Literature Review, 2025)
To ensure the legality of the transfer of land rights, the deed must be read; thus far, the Land Deed Making Officer has failed to read the sale and purchase deed to the presenter. The issue in this study is how the Court's decision on the Sale and Purchase Deed is not read, as well as the sanctions imposed on the Land Deed Making Officer for failing to read the deed in front of the Witness. This study employs both qualitative and normative methodologies. As a result of his carelessness in creating the sale and purchase deed, the Land Deed Making Officer who fails to read the deed is sanctioned by the code of ethics and civil or criminal law, which indirectly harms his career. The research findings also indicate that the deed is sued in court and loses its legal force.